Numerical simulation of fracture propagation and production performance in a fractured geothermal reservoir using a 2D FEM-based THMD coupling model. (15th June 2023) - Zhang, Bo; Guo, Tiankui; Qu, Zhanqing; Wang, Jiwei; Chen, Ming; Liu, Xiaoqiang
Abstract: Under the influence of tectonic stress and faults, there are many natural fractures (NFs) in hot dry rock (HDR) reservoirs. However, the effect of NFs on the propagation of hydraulic fractures (HFs) has often not been considered in previous studies. A coupled thermo-hydro-mechanical-damage (THMD) model by the finite element method is constructed to investigate hydraulic fracturing and production performance in a fractured geothermal reservoir. The results show that thermal stress and injection pressure jointly promote rock initiation and propagation. HF can propagate tortuously and deviate from the maximum horizontal stress direction under the influence of NFs. HF and open NFs constitute the main channel of heat transfer, which determines the heat extraction performance. The fluid viscosity ( μ ) and injection flow rate ( q in ) are the main factors affecting the fracturing and production performance. A higher μ and q in can significantly increase HF length and activate the NFs along the propagation path, so the fracture area and production temperature have a distant ascension. The horizontal stress difference (Δ σ ) and NF number ( n ) are secondary factors affecting the fracturing and production performances. A higher or lower Δ σ and n are not conducive to forming a long HF and enhancing the production temperature. A larger fracture area or higher fracture complexity does not necessarily lead to better production performance. For the development mode of HDR using two injection wells and one production well, it is beneficial to enhance the production temperature to give priority to ensuring the uniform propagation of HF. The results can provide a theoretical basis for the optimal design of an enhanced geothermal system in a fractured geothermal reservoir. Highlights: A coupled THMD model for the fracturing and production is constructed and verified HF propagation under the influence of NFs and the production performance are studied The main controlling factors affecting the fracturing and production are determined The uniform propagation of HF is beneficial to improve the production performance